Pengaruh Kompetensi dan Beban Kerja terhadap Kinerja Pelaksanaan Asuhan Keperawatan pada Bagian Rawat Inap Rumah Sakit Umum Dr Slamet Garut - Ineu Indriani (Jurnal Wacana Ekonomi, 2018)
Ineu Indriani, the influence of competence and workload on the performance of the implementation of inpatient nursing care. Carrying out the research under the guidance (name and title of doren pem 1) and (name n title pem 2), various efforts have been made so that the completion of this research. This research was conducted to determine the effect of competence partially on the performance of the implementation of inpatient nursing care, the effect of work load partially on the performance of the implementation of inpatient nursing care, the effect of competence and workload simultaneously on the performance of the implementation of inpatient nursing care at dr. Slamet Garut. This study used a sample of employees in the implementation of inpatient nursing care. The data used are primary data obtained by distributing research questionnaires. The data analysis technique used is multiple regression analysis. Data processing uses Statistical Product and Service Solutions (SPSS) version 20. The results showed that partially competence had a positive and significant effect on the performance of inpatient nursing care, workload had a negative and significant effect on the performance of inpatient nursing care. While simultaneously competence and workload have a significant effect on the performance of the implementation of inpatient nursing care.